Uji Antibakteri Getah Jarak Pagar dan Formulasi Sediaan Gel Getah Jarak Pagar Basis HPMC Sebagai Pengobatan pada Luka - Mulia Aria Suzanni; Raihanaton Raihanaton; Saudah Saudah; Septi Maulida (Jurnal Serambi Engineering, 2022)
Jatropha sap (Jatropha curcas Linn.) is a natural ingredient that contains active tannins, flavonoids and saponins. These metabolic compounds can help speed up the wound healing process. One way to increase the effectiveness of using Jatropha gum is to formulate Jatropha gum extract. This study aims to determine the formulation of gel preparations with varying concentrations of Jatropha gum using HPMC base, to determine the inhibitory power of Jatropha gum against bacteria E. coli and S. aureus. The results showed that Jatropha curcas sap was not able to inhibit the growth of E. coli but had activity to inhibit the growth of bacteria S. aureus. The inhibitory power at each concentration is 10% (8 mm), 25% (10 mm), 50% (11 mm) and 100% (13 mm). The gel preparations made were Formula F1, F2 and F3. The concentration of Jatropha gum used was 1%, 3% and 5%. The results showed that the gel was in semisolid form and had different gel colors based on the concentration of jatropha gum. The higher the concentration of jatropha gum, the more concentrated the gel color obtained.